The sport strategy of directorate of public education of elazi in 2023: Model suggestion - Çoban, Bilal; Karakaya, Yunus Emre (My University, 2011)
The target of this research is to introduce the present situation of the sports (Swot Analysis) within Directorate of Public Education of Elazi{dotless}? by meeting relevant individual and conducting surveys and as a result of this; this research aims to introduce the sport strategy of Directorate of Public Education of Elazi{dotless}? in 2023. While the data obtained from poll were analysed by the help of Windows package programme, Frequency analysis and percentage technique were used while analysing the data. In the findings obtained from the researches it is concluded that the sports institutions have a deficiency with the percentage of 3, 76 and the deficiency of sports device and equipments with the percentage of 3,69. As a result; by forming people who are expert in his area as Directorate of Public Education of Elazi{dotless}?, strategic targets that are in suggestion part have to be implemented instantly. Provided that these strategic targets are performed until 2023 that marks the century of the republic, Directorate of Public Education of Elazi{dotless}? will be the most developing institution in each part of the sport and it will be an example to other Directorate of Public Education in cities and districts.
Elazi? mi?llî e?i?tim müdürlü?ü'nün 2023 yili spor stratejisi Model önerisi
Keywords: 2023 year; Directorate of public education of elazi{dotless}?; Sport; Strategy; Swot analysis